دور استخدام نظم الاتِّصالات الإداريَّة في إدارة الأزمات المصرفيَّة "دراسة ميدانيَّة على المصارف العاملة في السَّاحل السُّوري" (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The objective of the research is to study the role of using management communication systems (quality of information in management communication systems, administrative communication skills, Principles and techniques of management communication systems) in banking crisis management in a sample of banks operating in the Syrian coast. The researcher distributed (80) questionnaires to managers, heads of departments, supervisors and administrative personnel responsible for taking various forms and types of administrative decisions in the banks under study. The number of recovered and valid questionnaires which were discharged was (77). The researcher analyzed the data using the Statistical Analysis Program (SPSS 25). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect on the use management communication systems (quality of information in management communication systems, administrative communication skills, Principles and techniques of management communication systems) in banking crisis management in the banks under study. The researcher also made a number of recommendations, including: The need to apply management communication systems in all Syrian institutions, the need to pay attention to the training of managers, decision makers and employees in the banks under study on the use of management communication systems and increase their knowledge in the areas of computer use and related programs, providing the necessary materials for the operation of management communication systems and keeping abreast of the technical developments in this field. هدف هذا البحث إلى دراسة مدى تأثير استخدام نظم الاتِّصالات الإداريَّة (جودة معلومات نظم الاتِّصالات الإداريَّة، مهارات الاتِّصالات الإداريَّة، أسس وتقنيات نظم الاتِّصالات الإداريَّة) في إدارة الأزمات المصرفيَّة، وذلك في عيِّنة من المصارف العاملة في السَّاحل السُّوري. قامت الباحثة بتوزيع (80) استبياناً على المديرين ورؤساء الأقسام والمراقبين وأفراد الكوادر الإداريَّة المسؤولة عن اتِّخاذ أشكال وأنواع مختلفة من القرارات الإداريَّة في المصارف محلِّ الدِّراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (77) استبانة. قامت الباحثة بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 25). وفي نهاية هذا البحث توصَّلت الباحثة إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي لاستخدام نظم الاتِّصالات الإداريَّة (جودة معلومات نظم الاتِّصالات الإداريَّة، مهارات الاتِّصالات الإداريَّة، أسس وتقنيات نظم الاتِّصالات الإداريَّة) في إدارة الأزمات المصرفيَّة في المصارف محلِّ الدِّراسة. كما تقدَّمت الباحثة في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: ضرورة تطبيق نظم الاتِّصالات الإداريَّة في جميع المؤسَّسات السُّورية، ضرورة الاهتمام بتدريب المدراء ومتَّخذي القرارات والعاملين في المصارف محلِّ الدِّراسة على استخدام نظم الاتِّصالات الإداريَّة وزيادة معارفهم بمجالات استخدام الحاسوب والبرامج ذات العلاقة، توفير المستلزمات المادِّيَّة الخاصة بتشغيل نظم الاتِّصالات الإداريَّة والمواكبة المستمرَّة للمستجدَّات التقنيَّة في هذا المجال.